Fill levels, cost comparisons, and expulsion force requirements of commonly used topical ophthalmic steroids. Issue 4 (April 2022) - Gill, Mohsain S.; Murphy, David A.; Dvorak, Justin D.; Shah, Simren V.; Riaz, Kamran M.
Abstract : Drop counts, fill levels, price per drop, price per milliliter, and expulsion force requirements varied significantly among branded vs generic and suspension vs gel formulations of commonly prescribed topical steroids. Abstract : Purpose: To determine volume fill levels, estimated costs, and force expulsion requirements per bottle of topical ophthalmic steroids commonly used in the United States. Setting: Tertiary care academic referral center. Design: Prospective laboratory investigation. Methods: 8 commercially available medications were tested: loteprednol 0.5%, loteprednol gel 0.5%, loteprednol gel 0.38%, difluprednate 0.05%, generic fluorometholone 0.1%, branded fluorometholone 0.1%, generic prednisolone 1.0%, and branded prednisolone 1.0%. 10 bottles of each medication were tested. A double-blinded method was used to measure actual bottle fill volume and number of drops dispensed per bottle. The total perioperative cost per drop was calculated for each medication using a mean cash price. Force requirements were measured using a customized force gauge apparatus. Formulations were compared using Kruskal-Wallis 1way analysis of variances. Results: All formulations were able to cover postoperative periods commensurate with commonly used dosing regimens for cataract surgery. All medications had greater than sticker volume. Loteprednol 0.5% suspension and branded fluorometholone had the highest and lowest number of drops among the medications tested, respectively. Loteprednol 0.38% gel was the most expensive medication, whereas generic prednisolone 1.0% was the least expensive. Gel and branded formulations of ophthalmic steroids required less expulsion force compared with other tested formulations. Conclusions: Volume fill levels, patient-incurred costs, and expulsion force requirements per bottle of topical steroid medications vary widely. Clinicians may wish to consider these findings when determining their perioperative prescribing regimen.